INTERNATIONAL CONFERENCE "EARLY AND INITIAL FOREIGN LANGUAGE LEARNING IN FORMAL EDUCATION" (Živi jezici: Journal for Foreign Languages and Literatures, 2016)
Report from the international conference "EARLY AND INITIAL LEARNING OF FOREIGN LANGUAGES IN FORMAL EDUCATION", held on February 7 and 8, 2016 at the Faculty of Philology, University of Belgrade.
Keywords: early foreign language learning; initial foreign language learning; formal education; international conference